Diseño De Un Modelo De Optimización Del Proceso De Soporte Técnico A Incidentes Informáticos Para La Empresa Net Computadores Ltda. (2023)
Technology today is one of the most important elements within an organization, therefore it is important to ensure its optimal operation and continuity of services, given this need, it is imperative to have an adequate management of incidents and requirements, to provide timely and effective solution to the requirements or incidents reported by users, this based on a series of methodologies and models applied within the process of technical support. Starting from a descriptive study with a mixed approach, the current process of the company Net Computadores Ltda is analyzed for the attention of incidents to its different customers, and the factors that influence the resolution times of the same, in turn, through a theoretical support of some frameworks and/or standards of good ITSM practices, an incident management model is designed that seeks to optimize the time and resources used in the current process and suggests some changes from the assignment of roles and a registration base that allows continuous improvement and customer satisfaction. Keywords: IT incident management, ITSM, support, systems, frameworks, service processes.